Severity of Acute Hepatitis and Its Outcome in Patients with Dengue Fever in Tertiary Care Hospital Rawalpindi - Zahid, Usama; Shazia Nisar; Saleem, Salman; Azeem, Abdul Rehman; Sadiq, Muhammad Arif; Aleem, Maira (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the severity and outcome of acute hepatitis in dengue patients.Study Design: Comparative cross-sectional study.Place and Duration of Study: Pak-Emirates Military Hospital, Rawalpindi Pakistan, from Dec 2022 to Oct 2023.Methodology: The study included 215 confirmed cases of dengue infection. Data included demographic details day of illness, clinical findings, laboratory parameters, duration of hospital stay, and mortality at the 20th day. Patients experiencing dengue complications such as bleeding and shock were monitored. We divided patients into two groups based on ALT levels: mild to moderate hepatitis with ALT levels up to 299 IU/L and severe hepatitis with ALT levels greater than 300 IU/.Results: A total of 215 patients with dengue fever were included in this study, out of which 184(83% were male) and 31(14% were female). Out of the total sample size, 181(86%) of patients had dengue fever, 75(33%) had dengue hemorrhagic fever, and 13(6%) had dengue shock syndrome. The study showed statistically significant differences in terms of bleeding in patients with mild/moderate hepatitis (median=109.50) and severe hepatitis (median=55.92), Z=2.52, p=0.012, r=0.174.Conclusion: This study concluded that severe hepatitis in dengue patients was associated with higher rates of dengue hemorrhagic fever and dengue shock syndrome. Severe hepatitis was also associated with decreased levels of platelets and higher rates of dengue complications like ascites and pleural effusion. It was also associated with a longer hospital stay.